Assessing the threat of mass casualty terrorism. - How, Siang Meng. (2008)
The nature of terrorism has changed in the post-Cold War era. The collapse of communism led to the demise of left-inclined terrorist groups predominant during that period. The vacuum was soon filled by new groups and individuals with fuzzy motivations. These post-modern terrorists bring with them new and more insidious threats. One of these is the increasing likelihood of mass casualty terrorism manifested through the use of weapons of mass destruction, particularly, chemical and biological weapons. Experts believe that biological weapons will be preferred by terrorists because of their greater lethality compared to chemical weapons. However, the Tokyo chemical gas attack in 1995 set a new precedent and model for terrorists to copy. Terrorists are now even more likely to stage a chemical weapons attack. Current responses in many countries to this nascent form of terrorism are inadequate. To meet the threat effectively, counter-terrorist measures must focus on building up prevention and mitigation measures. The consequences of such an attack are higher than a terrorist attack by traditional means and preparedness is the best defence against mass casualty terrorism.